Peran Perceived Organizational Support terhadap Work Engagement pada Karyawan Ekspatriat di PT. X - Satria Efandi; Ruqaya Annisa Nurul Haq (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
This study aims to examine the influence of Perceived Organizational Support (POS) on work engagement among expatriate employees at PT.X. This research employs a quantitative approach with a correlational survey design, involving 40 expatriate employees working in various countries. The research instrument consists of a questionnaire comprising the POS scale and the Work Engagement scale. The correlation analysis results show a significant positive relationship between POS and work engagement, with a correlation coefficient of r = 0.62 (p < 0.01). Linear regression analysis indicates that POS significantly predicts work engagement, with a regression coefficient β = 0.57 (p < 0.01), and POS accounts for 38% of the variance in work engagement. These results suggest that perceived organizational support plays a crucial role in enhancing expatriate employees' work engagement. These findings also support social exchange theory, which posits that employees who feel supported by their organization are more likely to reciprocate with higher levels of commitment and engagement. The practical implication of this study is the importance for multinational companies like PT.X to develop and strengthen support programs for expatriate employees to enhance their engagement and performance.